THE ISSUE OF WASTE TIRES IN ITACOATIARA-AM (REMUNOM, 2025)
This article aims to analyze the situation of end-of-life tires in the municipality of Itacoatiara-AM, as well as to present feasible alternatives for their environmentally appropriate disposal. The research employed both qualitative and quantitative approaches, including bibliographic review, technical visits, and the application of questionnaires to 19 vehicle maintenance establishments. The results show that most of the waste tires discarded in the city originate from motorcycles and are predominantly sent to the municipal open dump, with little adherence to recycling or reuse practices. It was also observed that there is a lack of effective public policies focused on reverse logistics and environmental education in the region, as well as the absence of companies specialized in tire recycling. Among the proposed alternatives are the creation of voluntary drop-off points, reuse incentives through educational campaigns, and the implementation of a local recycling plant. This initiative appears economically viable given the availability of raw material and the absence of direct competition. The implementation of integrated policies that involve public authorities, the private sector, and civil society is essential to improve the management of tire waste and to promote environmental sustainability in the municipality. The data highlight the urgency of structured actions to mitigate the environmental impacts of improper tire disposal, supporting the advancement of a circular economy and compliance with the guidelines of the National Solid Waste Policy.